First annual report - Nigeria Produce Marketing Co. Ltd. (Lagos Nigeria Produce Marketing Company Limited, 1964)
This report is aimed at presenting to the public the full record of the Company's activities.
osc 29/03/2019
Arch
Keywords: Produce Trade; Nigeria